Association of Serum Calcium and Insulin Resistance With Hypertension Risk: A Prospective Population‐Based Study. Issue 1 (8th January 2019) - Wu, Xiaoyan; Han, Tianshu; Gao, Jian; Zhang, Yunlong; Zhao, Shengnan; Sun, Rongbo; Sun, Changhao; Niu, Yucun; Li, Ying
Abstract : Background: The temporal sequence between serum calcium and insulin resistance (IR) and their effects on hypertension are unclear. We studied the association between serum calcium and IR, with risk of hypertension events in a longitudinal cohort conducted in China. Methods and Results: Data from 8653 subjects aged 20 to 74 years with an average follow‐up of 5.3 years were analyzed. Serum calcium, and fasting and 2‐hour serum glucose and insulin were measured at baseline and follow‐up. Cross‐lagged panel and mediation analysis were used to examine the temporal relationship between serum calcium and IR and its impact on hypertension incidence. The conjoint effects of serum calcium and IR at baseline on hypertension at follow‐up were observed ( P =0.029 for HOMA_IR [hepatic IR] and P =0.009 for Gutt index [peripheral IR]). The cross‐lagged path coefficient (β2 ) from baseline serum calcium to follow‐up peripheral IR were significantly greater than path coefficient (β1 ) from baseline peripheral insulin resistance to follow‐up serum calcium (β2 =−0.354 versus β1 =−0.005; P =0.027). However, no directional relationships were observed in the serum calcium↔hepatic IR analysis. The mediation effect of peripheral IR on the association of serum calcium at baseline with hypertension at follow‐up was estimated at 16.4% ( P <0.001). Conclusions: Our findings demonstrate that higher serum calcium levels probably precede peripheral IR, and this 1‐directional relation plays a role in the development of hypertension.